A review of potential critical factors in horse keeping for anaerobic digestion of horse manure. (November 2016) - Hadin, Åsa; Eriksson, Ola; Hillman, Karl
Abstract: Keeping horses causes environmental impacts through the whole chain from feed production to manure. According to national statistics, the number of horses in Sweden is currently 360, 000 and is continuing to increase. This result in increasing amounts of horse manure that has to be managed and treated, which is currently done using practices that cause local, regional, and global environmental impacts. However, horse manure and its content of nutrients and organic material could be a useful fertiliser for arable land and a substrate for renewable energy production as biogas. The aim of the paper is to identify and describe potentially critical factors in horse keeping determining the amount (total mass) and characteristics (nutrient content and biodegradability) of horse manure, and thus the potential for anaerobic digestion. A systematic combining approach is used as a structural framework for reviewed relevant literature. All factors identified are expressed as discrete choices available to the horse keeper. In all, 12 different factors were identified: type and amount of feed, type and amount of bedding, mucking out regime, residence time outdoors, storage type and residence time of manure in storage, spreading and soil conditions, and transport distance and type of vehicle fuel used. Managing horses in terms of these factors is of vital importance in reducing the direct environmental impacts from horse keeping and in making horse manure attractive as a substrate for anaerobic digestion. The results are also relevant to environmental systems analysis, where numerical calculations are employed and different biogas system set-ups are compared to current and other treatments. In such assessments, the relevance and importance of the critical factors identified here and corresponding conditions can be examined and the most promising system set-up can be devised.